Edmond Malinvaud: A tribute to his contributions in econometrics - Peter C. B. PHILLIPS (Institutional Knowledge at Singapore Management University, 2015)
Malinvaud stands as one of the enduring figures of 20th century economics. His passing is a sad and permanent loss to the French academy, to the profession at large, and to the world of econometrics where he reinstated in our discipline the rigor of the Cowles Commission researchers of the 1940s and delivered a unified thematic for the field that echoed the genius of Ragnar Frisch. Within the economics profession for several decades in the mid-twentieth century, the French economist Edmond Malinvaud stood virtually unchallenged in his mastery of our discipline, raising the central chambers of the modern edifice of quantitative economics to new heights of rigour and empirical relevance. His mission as an educator and researcher drew its motive power from the Ragnar Frisch mantra of unification, which had established a new frontier for the discipline where ideas from economic theory conjoined with mathematical method and statistical methodology to advance our understanding of economic activity and to illumine the implications of economic policy making.